Investigation effect of moderator role of using social media and social communication between skills of recognition and distinguish emotional facial expressions and social anxiety in relationship - Ermiş, Ece Naz; Kantarcı, Seda (My University, 2016)
The aim of this study is to determine the moderator effect of using social media between the relationship of recognition and distinguish skills of emotional facial expressions and social anxiety. The study was carried out on 187 university students who were selected randomly (in the range of 18-27 ages; female 134, male 53). Liebowitz Social Anxiety Scale (LSAS), Facial Emotion Identification and Discrimination tests (FID, FDSC) and demographical information form were used for data collection. In addition, participants were asked how many hours per day they use social communication and social media networks. Test of One Way Anova and analysis of multi-regression were used in analysis of data. The findings reveal that there wasn't statistically significant relationship between recognition skills of emotional facial expressions and social anxiety of university students. There was statistically significant relationship between distinguish skills of emotional facial expressions and social anxiety of university students. There was a meaningful effect of using social media as a moderator between distinguish skills of emotional facial expressions and social anxiety of university students. The results were discussed according to the limitations of the study and the suggestions were provided for future studies.
Keywords: Emotional Facial Expressions; Social media; Social Anxiety